2019
DOI: 10.1101/521963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the Dynamical Complexity underlying Meditation

Abstract: Over the past 2,500 years, contemplative traditions have explored the nature of the mind using meditation. More recently, neuroimaging research on meditation has revealed differences in brain function and structure in meditators. Nevertheless, the underlying neural mechanisms are still unclear. In order to understand how meditation shapes global activity through the brain, we investigated the spatiotemporal dynamics across the whole-brain functional network using the Intrinsic Ignition Framework. Recent neuroi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Given the novelty of our results with regards to the univariate stationarity and distributional properties of the data, there are no directly comparable studies within the meditation literature to help guide our interpretation. However, previous research has reported that experienced meditators in the meditation state show increased stability in the topographical pattern of EEG activity and in the temporal patterns of both EEG and fMRI based connectivity (Escrichs et al, 2019;Toutain et al, 2020;Vivot et al, 2020). The increased fMRI connectivity stability finding has also been reported in novice meditators, and for comparisons between meditator and non-meditator resting-state connectivity (Escrichs et al, 2019).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Given the novelty of our results with regards to the univariate stationarity and distributional properties of the data, there are no directly comparable studies within the meditation literature to help guide our interpretation. However, previous research has reported that experienced meditators in the meditation state show increased stability in the topographical pattern of EEG activity and in the temporal patterns of both EEG and fMRI based connectivity (Escrichs et al, 2019;Toutain et al, 2020;Vivot et al, 2020). The increased fMRI connectivity stability finding has also been reported in novice meditators, and for comparisons between meditator and non-meditator resting-state connectivity (Escrichs et al, 2019).…”
Section: Discussionmentioning
confidence: 88%
“…However, previous research has reported that experienced meditators in the meditation state show increased stability in the topographical pattern of EEG activity and in the temporal patterns of both EEG and fMRI based connectivity (Escrichs et al, 2019;Toutain et al, 2020;Vivot et al, 2020). The increased fMRI connectivity stability finding has also been reported in novice meditators, and for comparisons between meditator and non-meditator resting-state connectivity (Escrichs et al, 2019). Previous research has also shown that meditators generate more consistent brain activity in response to stimuli while performing a cognitive task, enabling their brain activity to time-lock more effectively to the stimuli presented in the task (Bailey et al, 2023b;Lutz et al, 2009).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation